Nanostructured VO2 (A) and VO2 (M) derived from VO2 (B): facile preparations and analyses of structural, thermal, optical and thermophysical properties - Barra, Hamdi Muhyuddin; Chen, Soo Kien; Tamchek, Nizam; Talib, Zainal Abidin; Lee, Oon Jew; Tan, Kar Ban (Kauno Technologijos Universitetas, 2021)
Vanadium dioxide (VO2) is an interesting compound that exists in different polymorphic phases with varying characteristics and potential applications. In this study, fabrication and property analyses of three VO2 polymorphs, namely VO2 (B), VO2 (A), and VO2 (M), are described. Specifically, VO2 (B) was prepared via hydrothermal method under a low synthesis temperature of 180 °C and a fast processing time of 24 h. In addition, VO2 (A) and VO2 (M) were derived from the as-synthesized VO2 (B) using sequential hydrothermal treatment and calcination process, respectively. From the fieldemission scanning electron microscope (FESEM) scans, belt-like VO2 (B) nanoparticles with dimensions of as low as 35 × 130 nm2 were formed. Further, hydrothermal treatment of the as-synthesized VO2 (B) resulted to a flower-shaped VO2 (A) due possibly to an oriented attachment mechanism. Meanwhile, annealing of the VO2 (B) sample caused granular growth that produced plate-like and oblate shaped VO2 (M) with dimensions of 135 to 306 nm in diameter and 28 to 37 nm in thickness. Moreover, the thermochromic properties of the samples were examined using differential scanning calorimetry (DSC) while the thermophysical properties of the samples were measured via microflash method. Accordingly, the prepared VO2 (A) and VO2 (M) samples exhibited phase transition behavior at 168.37 °C and 68.6 °C, respectively. Subsequently, changes in the thermophysical properties of each sample can be observed across the measured transition temperature. In particular, an increase in both the thermal diffusivity and thermal conductivity of VO2 (M) can be observed when the temperature was raised from 50 °C to 100 °C. On the other hand, there is a noticeable decrease in the thermal conductivity of VO2 (A) when the temperature was increased from 150 °C to 200 °C.